2008 16th IEEE International Requirements Engineering Conference 2008
DOI: 10.1109/re.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

Use and Influence of Creative Ideas and Requirements for a Work-Integrated Learning System

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
(20 reference statements)
0
27
0
Order By: Relevance
“…Evidence from our projects revealed that creative requirements are rarely generated directly, but result from transformations applied to artifacts acquired directly from stakeholders and other sources and often less novel and/or useful [29,32]. Therefore, as well as the need for more idea finding, other activities are also needed to generate creative requirements from new ideas.…”
Section: An Initial Agenda For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from our projects revealed that creative requirements are rarely generated directly, but result from transformations applied to artifacts acquired directly from stakeholders and other sources and often less novel and/or useful [29,32]. Therefore, as well as the need for more idea finding, other activities are also needed to generate creative requirements from new ideas.…”
Section: An Initial Agenda For Future Researchmentioning
confidence: 99%
“…Evidence suggests that most requirements generated in projects are similar to existing artifacts in the domain and not novel [29]. We depict these requirements in the bottomright quadrant.…”
Section: An Initial Agenda For Future Researchmentioning
confidence: 99%
“…Maiden et al [24] have discussed how creativity workshops in which a range of stakeholder representatives undertake activities using techniques such as constraint removal, brainstorming with creativity triggers and analogical reasoning can prompt participants to generate important ideas for requirements that are considered both novel and appropriate, and that may otherwise remain unexpressed. Jones et al [21] report on a workshop in a similar style that encouraged participants to brainstorm with creativity triggers, generate new ideas by removing constraints, and combine ideas about problems or requirements with other ideas about the application of new technologies; and Sustar et al [37] used similar techniques in workshops involving designers and older people in the design of digital devices.…”
Section: Stakeholder Creativity In Early Stage Design Workhopsmentioning
confidence: 99%
“…The same domain experts were also asked to rate each idea from 0 to 5 for appropriateness, based on the their view of the idea's usefulness within this domain and it's fit to the workshops' objective. This evaluation follows Sternberg and Lubart's [36] definition of creativity in terms of novelty and appropriateness, described earlier, and an approach to evaluation outlined in Dean et al [8] and previously used in Jones et al [21].…”
Section: Effectiveness Of Support For Creative Thinkingmentioning
confidence: 99%
“…Techniques for deliberately introducing creativity into the process of user-centered design can be used effectively in this context. For example, Schmid [46] used creativity triggers [42] to help workshop participants invent requirements, whilst co-creation [45] and creativity workshops [24,31] have been shown to be effective in generating novel requirements.…”
Section: Introductionmentioning
confidence: 99%